2021
DOI: 10.1126/sciadv.abg0390
|View full text |Cite
|
Sign up to set email alerts
|

The stability of R-spine defines RAF inhibitor resistance: A comprehensive analysis of oncogenic BRAF mutants with in-frame insertion of αC-β4 loop

Abstract: Although targeting BRAF mutants with RAF inhibitors has achieved promising outcomes in cancer therapy, drug resistance remains a remarkable challenge, and underlying molecular mechanisms are not fully understood. Here, we characterized a previously unknown group of oncogenic BRAF mutants with in-frame insertions (LLRins506 or VLRins506) of αC-β4 loop. Using structure modeling and molecular dynamics simulation, we found that these insertions formed a large hydrophobic network that stabilizes R-spine and thus tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…With BRAF, a secondary mutation in RS3 (L505H) induces resistance to vemurafenib [ 74 ]. Also, in another study resistance to dabrafenib or vemurafenib was demonstrated with BRAF L505H mutation [ 10 ]. Moreover, alectinib resistance was reported with I1171S and I1171N mutations in ALK [ 75 ].…”
Section: Mutations In Rs3 Exist Rarelymentioning
confidence: 99%
See 1 more Smart Citation
“…With BRAF, a secondary mutation in RS3 (L505H) induces resistance to vemurafenib [ 74 ]. Also, in another study resistance to dabrafenib or vemurafenib was demonstrated with BRAF L505H mutation [ 10 ]. Moreover, alectinib resistance was reported with I1171S and I1171N mutations in ALK [ 75 ].…”
Section: Mutations In Rs3 Exist Rarelymentioning
confidence: 99%
“…In the active state the location of RS2 as part of the assembled R-spine results in an open and extended conformation of the activation loop (A-loop), while a closed A-loop configuration is preferred in the inactive state. Notably, additional stabilization of the R-spine, such as via in-frame insertions or RS3 mutations [ 9 , 10 ], may result in increased catalytic activity of the protein kinase.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies have suggested that oncogenic RAF mutations might be classified as three groups: (1) highly constitutively active mutants such as BRAF(V600E) that directly phosphorylate MEK and thus activate downstream signaling cascade; (2) kinase-dead or -impaired mutants such as BRAF(V471F) that function as allosteric activators and switch on downstream signaling through triggering the catalytic activity of wild-type RAFs; and (3) intermediate active mutants such as BRAF(G469A) that have enhanced dimer affinity and directly turn on downstream signaling as homodimers [122][123][124] . However, there are some unique RAF mutants such as BRAF(ΔNVTAP), BRAF(L505H), and BRAF(LLR ins506 ) that do not fall into any of these categories [67,[125][126][127][128][129] , suggesting that oncogenic RAF mutations have diverse characters and complicated functional modes. Similar to RAS mutations, RAF mutations also have cancer-type preferences.…”
Section: Raf Mutationsmentioning
confidence: 99%
“…Indeed, these BRAF mutants have much less affinity for RAF inhibitors, suggesting instead that a stabilized R-spine leads to drug resistance. Given that R-spine can be stabilized by different mutations via various manners, we then determined whether other BRAF mutants with a stabilized R-spine such as L485F and L505H [127,128] were resistant to RAF inhibitors, and found that all these mutants were resistant to RAF inhibitors with different extents related to their R-spine stability. The R-spine stability can also explain why BRAF(V600E) splicing variants or other mutants with high dimer affinity are resistant to RAF inhibitors: a strong dimerization would lead to a cooperative assembly of R-spine in two protomers of a dimer, and hence R-spine held in a tight dimer is more stable than that in a lax dimer, which impairs drug engagement.…”
Section: Drug Resistance In Targeted Therapies With Raf Inhibitorsmentioning
confidence: 99%
“… 27 At this stage, a number of studies have adopted network pharmacology and molecular docking technology to explore the material basis and mechanism of action of Chinese medicine in treating certain diseases, and have determined the some of the underlying principles and feasibility of these technical methods. 30 …”
Section: Introductionmentioning
confidence: 99%